The Mediated Competitive Advantage Effect Of Brand Image, Customer Engagement, And Brand Reputation On Msme Performance - Ningsih, Wida (Universitas Gajah Putih, 2019)
The Covid-19 pandemic has had an impact on Micro, Small, and Medium Enterprises (Micro, Small, and Medium Enterprises), which has an impact on various sectors. According to the literature, it is known that the performance of SMEs can be improved by referring to the factors of brand image, customer engagement, brand reputation and competitive advantage. The purpose of this research is to determine the impact of brand image, customer engagement and brand reputation on MSME performance through competitive advantage. This is a causal study with a population of SMEs in the city of Bandung. The technique used is simple random sampling, which means that the entire population has the same thing to serve as the research respondents. The research sample includes 103 SMEs. This is a SEM-PLS study using the SmartPLS software. According to the study's findings, brand image and customer engagement have a significant positive effect on competitive advantage. Brand reputation has no bearing on competitive advantage. Customer engagement and competitive advantage have a significant positive impact on MSME performance. Brand image and brand reputation have no impact on MSME performance. Micro, Small, and Medium Enterprises can use customer engagement to gain a competitive advantage, which will ultimately improve their performance. There is a need for an evaluation of Micro, Small, and Medium Enterprises' brand image and reputation, and Micro, Small, and Medium Enterprises can recognize that brand image and reputation is an asset that can improve their performance.